2016
DOI: 10.1134/s2075113316030102
|View full text |Cite
|
Sign up to set email alerts
|

Structure and shear strength of implants with plasma coatings

Abstract: Four types of three dimensional plasma capillary porous titanium coatings for model intraosseous implants are developed. By means of pulsed microplasma oxidation in solutions or plasma spray ing of powders, additional bioactive coatings on the basis of calcium phosphates are deposited on the Ti coat ing surface. Shear strength values of the interface between the implants coated and osseous block after 16 weeks of implantation are 4.25-4.81 MPa, while for implants with additional plasma hydroxyapatite coat ing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Manley et al [ 36 ] found that the fatigue shearing strength of bead-sintered coating-substrate interfaces was similar to or less than that between coating and bone. An in vivo study found shearing strength at the bone-implant interface was between 4.25 and 7.81 MPa for plasma-sprayed, porous Ti coatings [ 31 ]. An in vitro analysis [ 24 ] of Ti porous coat-substrate interfaces found static shear strength to be greater than 20 MPa, on average; this same report showed the coating can withstand fatigue shear forces of 10 MPa for at least 10 7 cycles, per the ASTM F1160 standard [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Manley et al [ 36 ] found that the fatigue shearing strength of bead-sintered coating-substrate interfaces was similar to or less than that between coating and bone. An in vivo study found shearing strength at the bone-implant interface was between 4.25 and 7.81 MPa for plasma-sprayed, porous Ti coatings [ 31 ]. An in vitro analysis [ 24 ] of Ti porous coat-substrate interfaces found static shear strength to be greater than 20 MPa, on average; this same report showed the coating can withstand fatigue shear forces of 10 MPa for at least 10 7 cycles, per the ASTM F1160 standard [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a relatively new method of valve metals surface refinementthe method of electrolytic plasma refinement (EPR) is of interest. The EPR is peculiar to the surface micro discharge involvement into the process of surfacing, having a substantial specific effect on the surfaces under development [1][2][3][4][5][6][7].…”
Section: исследование физико-механических свойств оксидных покрытий нmentioning
confidence: 99%
“…Given this, the method of plasma electrolytic oxidation (PEO), a relatively new method used to treat the valve metals surface, is of interest [1][2][3]. A characteristic feature of PEO is the use of surface microdischarges to form a coating having a very significant and specific effect on the coating formed [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%